2018
DOI: 10.1002/cam4.1351
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐634 sensitizes glioma cells to temozolomide by targeting CYR61 through Raf‐ERK signaling pathway

Abstract: Glioma is the most common intracranial malignant tumors, accounting for about 40% of intracranial tumors. Primary or secondary drug resistance is one of the main reasons for the failure of treatment. The oncogenic or tumor‐suppressive roles of miR‐634 have been revealed in different types of cancer. However, the role of miR‐634 in glioma remains unknown and whether miR‐634 could sensitize glioma cells to temozolomide also is unclear. Here, we aim to investigate the biological function of miR‐634 and the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Abnormal expression of miRs has been considered to impact cancer progression. Several studies have revealed that miR-634 functions as a biomarker and has significant roles in various types of cancer, including glioma, gastric carcinoma, hepatocellular carcinoma, nasopharyngeal carcinoma, ovarian cancer and cervical cancer (712). However, to the best of our knowledge, no study has investigated the role of miR-634 in PC thus far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal expression of miRs has been considered to impact cancer progression. Several studies have revealed that miR-634 functions as a biomarker and has significant roles in various types of cancer, including glioma, gastric carcinoma, hepatocellular carcinoma, nasopharyngeal carcinoma, ovarian cancer and cervical cancer (712). However, to the best of our knowledge, no study has investigated the role of miR-634 in PC thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to the best of our knowledge, the present study provided evidence for the first time that miR-634 can suppress PC cell growth by inhibiting HSPA2. Notably, miR-634 can regulate other genes, including CYR61, JAG1, Rab1A and DHX33 (79); therefore, further assessment of the molecular mechanism of miR-634 in PC is required. A recent study has revealed that miR-634 could directly regulate Jagged 1 expression in gastric cancer (8); however, the present study failed to identify any significant association between miR-634 and JAG1 in PC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al pointed out that miR-634 could increase cell sensitivity to temozolomide through the Raf-ERK pathway by targeting CYR61 in glioma. 33 Another study demonstrated that miR-634 elevated the radiosensitivity of breast cancer cells through downregulating STAT3. 34 MiR-634 has been revealed to exert a suppressive role in gastric cancer, 16 pancreatic cancer, 17 hepatocellular cancer, 35 and CC.…”
Section: Discussionmentioning
confidence: 99%
“…There is also proof of the functioning of miRNAs in the resistance to chemotherapeutic agents via their influence on the uptake, metabolism, targeting of the drug or influencing apoptosis or repair mechanisms or the cell cycle . This is highlighted by an example of lowered TMZ resistance by boosting miR‐634 to target CYR61 to in turn affect the Raf‐ERK circuit in glioma . Oncogenesis is augmented by numerous tumour suppressor genes that are the target of miR‐21: that happens to be among the first discovered miRNAs in humans .…”
Section: Introductionmentioning
confidence: 99%